2023
DOI: 10.3390/ijms241713191
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Pro-Survival and Pro-Regenerative Effects of Conditioned Medium from Wharton’s Jelly Mesenchymal Stem Cells on Developing Zebrafish Embryos

Chiara Reina,
Clara Cardella,
Margot Lo Pinto
et al.

Abstract: Conditioned media harvested from stem cell culturing have the potential to be innovative therapeutic tools against various diseases, due to their high content of growth, trophic and protective factors. The evaluation in vivo of the effects and biosafety of these products is essential, and zebrafish provides an ideal platform for high-throughput toxicological analysis, concurrently allowing the minimization of the use of mammalian models without losing reliability. In this study, we assessed the biological effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In a derivative study ( Reina et al, 2023 ), we assessed the biological effects in vivo elicited by exposure to the conditioned medium preparations described here. Intriguingly, by using the zebrafish model we found that conditioned medium treatment triggers multiple favourable outcomes in vivo , including antioxidant, anti-apoptotic and pro-regenerative effects, impinging on specific marker gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In a derivative study ( Reina et al, 2023 ), we assessed the biological effects in vivo elicited by exposure to the conditioned medium preparations described here. Intriguingly, by using the zebrafish model we found that conditioned medium treatment triggers multiple favourable outcomes in vivo , including antioxidant, anti-apoptotic and pro-regenerative effects, impinging on specific marker gene expression.…”
Section: Discussionmentioning
confidence: 99%